Report on CTA’s Intellectual Legacy Assets - Khadar, Ibrahim (Technical Centre for Agricultural and Rural Cooperation, 2020)
The Cotonou Partnership Agreement between the European Union (EU) and the Organisation of the African, Caribbean and Pacific States (OACPS) countries, the legal and financial framework that supported the Technical Centre for Agricultural and Rural Cooperation (CTA), was due to end on 28 February 2020. As a consequence, CTA was also set to close. An orderly closure of the Centre was agreed by the OACPS-EU authorities, with the process to run from March to December 2020. As the negotiations on the future agreement between the OACPS and EU were delayed, the parties agreed on transitional measures to extend the application of the Cotonou Agreement first until December 2020 and later until November 2021. Although the process of closing CTA continued into 2021, the work described in this report was carried out between March and December 2020. Established in 1983, CTA actively supported agricultural transformation in African, Caribbean and Pacific (ACP) countries for over 35 years, with wide ranging results and uptake of innovative practices in nearly 80 countries. Over the years, CTA adapted its approaches from its original role as a knowledge broker to driving wider investments, promoting innovation exchange on technologies, digital solutions, business models and relationships that have been critical to the sustainable transformation of ACP agriculture and the improvement of food and nutrition security. These decades of investments have yielded impressive results, a strong reputation and a rich intellectual property legacy, most of which is extremely useful to ACP agriculture and the development sector. Although CTA as an institute will cease to exist, the Centre has made every effort to ensure that its rich portfolio of valuable intellectual assets remain global public goods and continue to be available publicly to those that can benefit from them. As part of the orderly closure process, the Centre’s management instituted a process to take stock of its intellectual legacy assets and plan for their responsible transfer, retention or disposal, in close consultation with EU and ACP stakeholders. This included a comprehensive plan for handling these assets, which was approved by the EU and CTA’s Executive Board.